Adverse effects of erenumab on cerebral proliferative angiopathy: A case report. (January 2021) - Lehman, Laura L; Bruccoleri, Rebecca; Danehy, Amy; Swanson, Julie; Mrakotsky, Christine; Smith, Edward; Orbach, Darren B; Burstein, Rami
Background: Cerebral proliferative angiopathy is a vascular malformation associated with compromised blood-brain barrier and with migraine-like headache. Treating blood-brain barrier-compromised patients with erenumab, an anti-calcitonin gene-related peptide receptor monoclonal antibody, may be risky. Case: We describe a case of a 22-year-old chronic migraine patient with cerebral proliferative angiopathy who presented to our hospital in status epilepticus 2 d after his first dose of erenumab. Serial magnetic resonance imaging (MRI) studies demonstrated progressive areas of diffusion restriction including the brain tissue adjacent to the cerebral proliferative angiopathy, bilateral white matter and hippocampi. His 6-month post-presentation magnetic resonance imaging was notable for white matter injury, encephalomalacia surrounding cerebral proliferative angiopathy and bilateral hippocampal sclerosis. He remains clinically affected with residual symptoms, including refractory epilepsy and cognitive deficits. Conclusion: The evidence presented in this case supports further investigation into potential deleterious side effects of erenumab in patients with compromised blood-brain barrier, such as individuals with intracranial vascular malformations.